Urgency Historical Tracing Reality Double-Entry Bookkeeping - Amir, Vaisal; Alfia, Yulis Diana (Politeknik Negeri Madiun, 2021)
This study aims to explore the urgency of history exploration of Double-Entry Bookkeeping reality and methodology. The method used in this research is a critical literature study. The results showed that there is a fundamental issue (basic) in viewing of the general development of accounting (positivism) who sees accounting simply as numbers and technical bookkeeping. These views are binary (single vision) that is patterned secularist materialism. Positivism is seen as constraction view of reality and resulted in a crisis of ethics. In the history of the literature review found that precisely the development of accounting that claim construction Double-Entry Bookkeeping Paciolli as accounting embryo today is unhistorical. DEB historical studies tend to use the basis of conventional economic paradigm and functionalist explanation. Methodological exploration in the history of accounting needs to be done in finding accounting reality DEB relevant and contextual to its day. Methodological aspects of multidisciplinary and use this critical perspective is required in order to occur the dynamic changes in the accounting, understanding, and development of accounting more ethical and just.